Chain‐growth polycondensation via the substituent effect: Investigation in to the role of initiator and base on the synthesis of poly(N‐octyl benzamide). Issue 17 (16th August 2020) - Prehn, Frederick C.; Etz, Brian D.; Price, Daniel; Trainor, Amanda; Reese, Caleb J.; Vyas, Shubham; Boyes, Stephen G.
Abstract: A detailed investigation into the role of initiator structure, the presence of an initiator, and basicity of the non‐nucleophilic base in the chain‐growth condensation (CGC) synthesis of poly( N ‐octyl benzamide) was conducted. A series of phenyl ester dimethyl amide initiators with different leaving groups were synthesized and used in the CGC preparation of poly( N ‐octyl benzamide). Additional polymerizations were conducted without the presence of an initiator and with different non‐nucleophilic bases. Kinetic studies, along with nuclear magnetic resonance spectroscopy and gel‐permeation chromatography, were used to determine progress of the reaction, molecular weights, and molecular weight distributions. The experimental and computational results demonstrated that initiators containing electron‐withdrawing substituent phenyl esters, such as the p‐nitrophenyl ester, and electron‐withdrawing carbonyl character on the parent benzoate produce polymers with controllable molecular weights and narrow molecular weight distributions. Whereas, initiating species that contain electron‐donating character on the benzoate backbone, such as dimethylamino and methyl ester groups, produce polymers that resemble the results from reactions involving no initiators at all, indicating poor polymerization control. Abstract : A detailed study into the effect of base and initiator on chain‐growth polycondensation reaction for the synthesis of poly( N ‐octyl‐benzamide) is conducted. Through experimental and computational results, it is demonstrated that the initiator structure, in conjunction with base strength, plays a dominant role in limiting self‐initiation and producing well‐defined polymers.